2014
DOI: 10.2807/1560-7917.es2014.19.4.20684
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based syndromic monitoring of acute respiratory illness in the general population of Germany, weeks 35/2011 to 34/2012

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 11 publications
(1 reference statement)
0
39
0
2
Order By: Relevance
“…The first method consisted of dropping each participant's first report to the system to account for first-time user error and nonserious reporting, because similar methods are employed by other participatory surveillance systems. 1,6 We designed the second method specifically to filter out undesired spikes observed in the unadjusted FNY influenza-like illness rates. By analyzing historical weekly changes in CDCreported ILI rates with respect to the preceding 4 weeks from December 2002 to October 2011, we observed that changes in CDC influenza-like illness rates typically (99% of the times) fell within -10 and 10 SDs from the mean change of the previous 4 weeks.…”
Section: Data Management and Analysismentioning
confidence: 99%
“…The first method consisted of dropping each participant's first report to the system to account for first-time user error and nonserious reporting, because similar methods are employed by other participatory surveillance systems. 1,6 We designed the second method specifically to filter out undesired spikes observed in the unadjusted FNY influenza-like illness rates. By analyzing historical weekly changes in CDCreported ILI rates with respect to the preceding 4 weeks from December 2002 to October 2011, we observed that changes in CDC influenza-like illness rates typically (99% of the times) fell within -10 and 10 SDs from the mean change of the previous 4 weeks.…”
Section: Data Management and Analysismentioning
confidence: 99%
“…To estimate the burden of disease on population level due to acute respiratory infections (ARI), influenza‐like illness (ILI) or influenza in particular Internet‐based, participatory surveillance systems have been set up in the last 15 years in several countries within and outside of Europe . In Germany, a system called GrippeWeb has been launched in 2011 . Advantages of GrippeWeb include that it works year‐round and generates representative data in all age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of GrippeWeb include that it works year‐round and generates representative data in all age groups. Moreover, as GrippeWeb also collects information if a person with ARI consults a physician for his or her illness GrippeWeb data on “ARI with ensuing consultation of a primary health care provider” could be successfully compared and cross‐validated with data on “physician consultations due to ARI” generated by the German sentinel physician network “Arbeitsgemeinschaft Influenza” (AGI) …”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these systems, the Skoll Global Threats Fund (SGTF) and HealthMap of Boston Children’s Hospital partnered to launch “Flu Near You” in the United States in 2011 [19,25]. All three systems aim to track ILI through capturing symptom-based reports from volunteers on a weekly basis and have demonstrated a strong correlation with trends seen in traditional influenza surveillance systems in their respective countries [18,19,26,27]. Since Fall 2015, the Public Health Agency of Canada has been piloting a similar influenza-focused system, the “FluWatchers” platform [28].…”
Section: Resultsmentioning
confidence: 99%